Dhwajastambh (flagstaff) at the Vetal Dev Temple - Mumbai Archive Project Team (Jio Institute, 2024)
Pictured here is the flagstaff (dhwajastambh) at the Vetal Dev Temple. The saffron flag, which is visible from a long distance, symbolizes the presence of the divine.